PENGARUH GAYA HIDUP, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI SRC ALIANG - Kustina, Harianti; MARDIKA, NANDA HARRY (LPPM Universitas Putera Batam, 2021)
the ease of starting a business makes competition in the same field tighter so that each company has its own characteristics. Each company usually has their own differences which are the determining factors in purchasing decisions. consumers' selective attitude in buying encourages companies to provide something that is best in accordance with consumer desires. Each person's purchasing decision is different, depending on each person. it depends on what they care about buying the product. There are some people who prefer a brand image that they consider good and the quality of the service provided by the company is satisfactory. A purchase decision also depends on the lifestyle of the consumer itself because it represents the attitude of consumers in determining their wants and needs. Therefore, the aim of this research is to prove whether there is an effect of lifestyle, brand image and service quality on purchasing decisions at SRC ALIANG. This type of research is descriptive research with quantitative methods. With the results obtained, it is stated that the lifestyle, brand image and service quality have partially and simultaneously influences purchasing decisions at SRC ALIANG.